AN OPTIMISATION-BASED DECISION SUPPORT SYSTEM FRAMEWORK FOR MULTI-OBJECTIVE IN- CORE FUEL MANAGEMENT OF NUCLEAR REACTOR CORES - Schlünz, Evert Barend; Bokov, Pavel M; van Vuuren, Jan Harm (The South African Journal of Industrial Engineering, 2016)
The notion of in-core fuel management (ICFM) involves decision making in respect of the specific arrangement of fuel assemblies in a nuclear reactor core. This arrangement, referred to as a reload configuration, influences the efficiency and effectiveness of fuel usage in a reactor. A decision support system (DSS) may assist nuclear reactor operators in improving the quality of their reload configuration designs. In this paper, a generic optimisation-based DSS framework is proposed for multi-objective ICFM, with the intention of serving as a high-level formalisation of a computerised tool that can assist reactor operators in their complex ICFM decisions.